2009
DOI: 10.1297/cpe.18.81
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Male Patient with Fibular Aplasia, Tibial Campomelia and Oligodactyly': An Additional Case Report

Abstract: We report a male infant with FATCO syndrome, an acronym for fibular aplasia, tibial campomelia, and oligosyndactyly. Courtens et al. reported an infant with oligosyndactyly of the left hand, complete absence of the right fibula, bowing of the right tibia, and absence of the right fifth metatarsal and phalanges. They noted 5 patients with similar clinical features, and proposed the FATCO syndrome. Our patient had a left-sided cleft lip, cleft palate, oligosyndactyly of the right hand and bilateral feet, and bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 16 publications
4
41
0
4
Order By: Relevance
“…However, they categorised the case as Fuhrmann syndrome although Fuhrmann has femoral but not tibial bowing [14]. Kitaoka et al, reported bilateral oligodactyly and tibial campomelia but unilateral fibular aplasia [13]. Our case it the first case of proven FATCO syndrome with bilateral malformations.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, they categorised the case as Fuhrmann syndrome although Fuhrmann has femoral but not tibial bowing [14]. Kitaoka et al, reported bilateral oligodactyly and tibial campomelia but unilateral fibular aplasia [13]. Our case it the first case of proven FATCO syndrome with bilateral malformations.…”
Section: Discussionmentioning
confidence: 64%
“…Some had femoral bowing or polidactyly but only Hecht et al, and Lazjuk et al, described this syndrome in female patients [11,12]. Also, several reported patients have other malformations beside described three -fibular aplasia, tibial campomelia and olygodactyly [11][12][13]. Whether this represents a variability in the same syndrome or appearance of other malformations beside FATCO syndrome needs to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Se cree que el síndrome FATCO se da por alteración en el eje dorso-ventral y en la parte distal de la pierna. 4,5,[8][9][10] Una de las características del síndrome FATCO es la malformación en la fíbula. Este tipo de malformaciones son raras, pero son las más comunes entre las malformaciones óseas de los miembros inferiores.…”
Section: Discussionunclassified
“…La mayoría de las veces, se presenta una agenesia fibular aislada, hecho que sugiere teratogenicidad o causas no genéticas. 1,4,5,11,12 La malformación en la fíbula también es parte del síndrome de aplasia fibular con ectrodactilia (ausencia de partes de los dedos o los dedos completos), que puede ser asociada a alteraciones faciales. La ectrodactilia asociada al síndrome FATCO también se encuentra como parte de la malformación denominada mano-pie en hendidura (split hand/foot malformation), la cual se caracteriza por la ausencia de metacarpos y/o metatarsos, sindactilia de los dedos restantes y, en ocasiones, hipoplásicos.…”
Section: Discussionunclassified
See 1 more Smart Citation